Harmony as a Teacher's Approach to Addressing Bullying in School - Shirrly Fitrianingrum; Sri Lestari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Bullying in schools negatively impacts the physical and mental health of adolescents, as well as their academic performance. Social support from teachers plays a crucial role in mitigating these effects. One effective approach that can be taken is teaching the values of harmony. This research aims to explore how teachers address bullying through the implementation of harmonious values. Methodology: The study involved three teachers who provided support to students who had experienced bullying. Participants were recruited using a snowball sampling technique. This research used a descriptive qualitative approach. Data collected through semi-structured interviews and analyzed thematically. Data credibility was ensured through member checking. Results: The findings revealed that teachers taught harmonious values and applied them in addressing bullying cases. Methods included fostering empathy and creating a harmonious atmosphere among peers. This approach led to improved psychological well-being for victims of bullying and a more harmonious classroom environment.Applications/Originality/Value: The implication is that practicing harmonious values can serve as a practical tool and foundation for anti-bullying policies in schools.